1999
DOI: 10.1002/etc.5620180820
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and desorption characteristics of aged, nonextractable atrazine in soil

Abstract: The bioavailability and desorption characteristics of nonextractable soil‐aged atrazine were investigated to examine the significance of this potentially large contaminant fraction in agricultural soils. Radiolabeled atrazine‐applied soil was aged for 3 months and then extracted by one of three methods—methanol‐water (4: 1) at 75°C, acetone, and artificial soil water—representing a range of extraction efficiencies. Viable microcosms were constructed with the dried, extracted soil to compare rates and extents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…As described, efficient biotransformation of TNT to ADNTs also was reported for freshwater fish, including channel catfish and fathead minnow . Efficient biotransformation of TNT to ADNTs additionally has been observed in marine fish (including sheepshead minnow ), in multiple invertebrates , and in another amphibian, the tiger salamander ( Ambystoma tigrinum ) . Similar to the observations found in tadpoles in the present study, formation of DANTs resulting from exposure to TNT reported in the studies cited above was non‐quantifiable or minimal.…”
Section: Discussionsupporting
confidence: 89%
“…As described, efficient biotransformation of TNT to ADNTs also was reported for freshwater fish, including channel catfish and fathead minnow . Efficient biotransformation of TNT to ADNTs additionally has been observed in marine fish (including sheepshead minnow ), in multiple invertebrates , and in another amphibian, the tiger salamander ( Ambystoma tigrinum ) . Similar to the observations found in tadpoles in the present study, formation of DANTs resulting from exposure to TNT reported in the studies cited above was non‐quantifiable or minimal.…”
Section: Discussionsupporting
confidence: 89%
“…The proportions of extractable 14 C‐residues decreased during the incubations in the four soils (Table 2) In S1, this decrease was more pronounced supporting the idea that the extractable fraction was the most available for microbial degradation (Johnson et al, 1999). The evolution of the extractable residues in the soils without field atrazine application under no‐tillage (S2) and conventional tillage (S3) was similar, while the smallest proportion of extractable 14 C residues at the end of the incubation period was found in the brushwood soil (S4).…”
Section: Resultsmentioning
confidence: 59%
“…It is common to spike soil with the study compound(s) and subsequently extract the whole spiked soil mass when investigating the binding, sequestration, extractability, and bioavailability of organic compounds in soil (Chung and Alexander, 1998; Hatzinger and Alexander, 1995; Johnson et al, 1999; Kelsey et al, 1997; Kohl and Rice, 1998; Nam et al, 1998; Nieman et al, 1999; Tang et al, 1998; White et al, 1997). While extracting the total mass of spiked soil undoubtedly decreases the variability in the experimental data, the heterogeneous distribution of contaminants, organic matter, and microbial populations in soil environments is neglected.…”
Section: Discussionmentioning
confidence: 99%